2013 IEEE International Conference on Computational Intelligence and Virtual Environments for Measurement Systems and Applicati 2013
DOI: 10.1109/civemsa.2013.6617393
|View full text |Cite
|
Sign up to set email alerts
|

Accurate 3D fingerprint virtual environment for biometric technology evaluations and experiment design

Abstract: Abstract-Three-dimensional models of fingerprints obtained from contactless acquisitions have the advantages of reducing the distortion present in traditional contact-based samples and the effects of dirt on the finger and the sensor surface. Moreover, they permit to use a greater area for the biometric recognition.The design and test of three-dimensional reconstruction algorithms and contactless recognition methods require the collection of large databases. Since this task can be expensive and timeconsuming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…-Less-constrained recognition could increase the usability and social acceptance of biometric systems [70]. In fact, since they allow a touchless recognition, it would be possible to perform the biometric verification at higher distances, with natural light conditions, and while the traveler is moving, by using the fingerprint [34,35,41,33,30,29,26,39,25,32], the palm [59], or the iris [70,42,27,76,75,37]. A study showed that touchless fingerprint technologies would be preferred over touch-based systems [35], thus allowing for an increased confidence and adoption of biometric recognition [43].…”
Section: Challengesmentioning
confidence: 99%
“…-Less-constrained recognition could increase the usability and social acceptance of biometric systems [70]. In fact, since they allow a touchless recognition, it would be possible to perform the biometric verification at higher distances, with natural light conditions, and while the traveler is moving, by using the fingerprint [34,35,41,33,30,29,26,39,25,32], the palm [59], or the iris [70,42,27,76,75,37]. A study showed that touchless fingerprint technologies would be preferred over touch-based systems [35], thus allowing for an increased confidence and adoption of biometric recognition [43].…”
Section: Challengesmentioning
confidence: 99%